1993
DOI: 10.1029/93ja00605
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic ion cyclotron waves stimulated by modest magnetospheric compressions

Abstract: The relationship between sudden impulses and enhancements or onset of Pc 1 at high-latitude ground stations is well established. It has been proposed that increased hot proton temperature anisotropy resulting from convection during magnetospheric compression is responsible for the enhancement in Pc 1 emissions via generation of electromagnetic ion cyclotron (EMIC) waves in the dayside outer equatorial magnetosphere (e.g., Olson and Lee, 1983). We use AMPTE/CCE magnetic field and particle data to test this sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
256
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(280 citation statements)
references
References 23 publications
21
256
3
Order By: Relevance
“…When the L-value is normalized to the magnetopause position L mp , the highest probabilities of Pc 1 wave occurrence are close to the magnetopause, with P wav ∼ 0.25 for L norm ≡ L/L mp = 0.8-1.0. These results are consistent with increased convective growth rate at large L (Anderson et al, 1992a), and with the greater effect of magnetosphere compression close to the magnetopause (Anderson and Hamilton, 1993). On the other hand, we only directly observe magnetic field compression for at most about 25% of the wave events.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…When the L-value is normalized to the magnetopause position L mp , the highest probabilities of Pc 1 wave occurrence are close to the magnetopause, with P wav ∼ 0.25 for L norm ≡ L/L mp = 0.8-1.0. These results are consistent with increased convective growth rate at large L (Anderson et al, 1992a), and with the greater effect of magnetosphere compression close to the magnetopause (Anderson and Hamilton, 1993). On the other hand, we only directly observe magnetic field compression for at most about 25% of the wave events.…”
Section: Discussionsupporting
confidence: 78%
“…At most, about 25% of the observed Pc1 events were associated with enhancements (of at least ∼ 15%) in the magnetic field, which may indicate compressions. Anderson and Hamilton (1993) observed that when the AMPTE/CCE data are screened to include only times of magnetospheric compressions, the Pc 1 occurrence rate was enriched from the normal value ∼ 20-25% to 63%. Our data would be consistent with those of Anderson and Hamilton if such compressions occur about 10% of the time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compression of the magnetopause is suggested as another possible source of EMIC waves [e.g., Anderson and Hamilton, 1993;McCollough et al, 2012;Usanova et al, 2008]. While it is frequently thought that EMIC emissions are generated along the field line at the equatorial source region particularly in the inner magnetosphere, information about the wave normal angle of EMIC waves is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…A short time later, electromagnetic waves in the Pcl (0.2-0.5 Hz) frequency range are often observed in the magnetosphere [Anderson and Hamilton, 1993] Kangas et al, 1986Kangas et al, , 1998]. The excitation of Pcl emissions in the wake of Sis is explained by compressions of the magnetosphere under the action of interplanetary shocks [Olson and Lee, 1983].…”
Section: Introductionmentioning
confidence: 99%